If others drive intoxicated, so may I: Determinants for young drivers in Bulgaria. (January 2022) - Vankov, Daniel; Chiers, Johan; Vankov, Borislav
Highlights: Young drivers' behaviour is influenced by whether their important referents DUI. 15% of respondents report DUI in the past three months. DUI in young drivers exhibit a strong intentions-behaviour relationship. TPB has sufficient predictive power in structural equation modelling. An impulsivity profile can help tailor interventions to higher-risk individuals. Abstract: Young drivers' crash risk increases as a result of driving under the influence of drugs or alcohol (DUI) due to impaired driving. There is little evidence about the DUI determinants in middle-income countries, such as Bulgaria, a gap addressed by this article. The study used an online survey to obtain data from a sample of young Bulgarian drivers aged 18–25. The survey was designed to extend the Theory of Planned Behaviour (TPB). A base (TPB only) and an extended (TPB plus additional predictors) model were assessed to predict the participants' DUI. The predictors were investigated separately for the whole sample (n = 533, a logistic regression) as well as for the participants who DUI in the past three months (n = 83, a partial least squares structural equation modelling). The models were a good fit for the data. Both models predicted statistically significant amounts of variance in DUI intentions (whole sample: base model between 16.6% and 29.1%, extended model between 23.1% and 40.5%; higher-risk subsample: base model 56%, extended model 60%) and past DUI behaviour (whole sample: base model between 12.8% and 22.1%, extended model between 20.1% and 34.7%; higher-risk subsample: base model 50%, extended model 64%). DUI intentions consistently significantly predicted past DUI behaviour. Descriptive norm was the other consistent significant predictor of both DUI intentions and past DUI behaviour across all analyses. This new knowledge of understanding DUI determinants may help researchers and practitioners meet the safety needs of young drivers better, both in Bulgaria and in the European Union.